2017
DOI: 10.3390/nu9101074
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Evaluation of Dietary Intake in Patients with Non-Alcoholic Steatohepatitis

Abstract: There are very few reports about the intake of nutrients for the development or progression of non-alcoholic steatohepatitis (NASH). The aim of this study was to identify the dietary habits and the nutrient intake in patients with NASH, in comparison to chronic hepatitis C (HCV)-related patients. We prospectively evaluated the intake of macronutrients and micronutrients in 124 NAFLD and 162 HCV patients, compared to 2326 subjects as a control group. We noticed major differences in macro- and micronutrients int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 73 publications
(80 reference statements)
3
11
0
2
Order By: Relevance
“…The first hit of lipid deposition in the liver is induced via dietary intake. Advanced NAFLD patients have been shown to consume more carbohydrates/energy higher saturated fatty acid and lower polyunsaturated fatty acids [77,78]. Adipose tissue in NAFLD produces adipokines, such as tumor necrosis factor alpha (TNFα), resistin, and adiponectin.…”
Section: Oxidative Stress In the Pathogenesis Of Nafld-related Steatomentioning
confidence: 99%
“…The first hit of lipid deposition in the liver is induced via dietary intake. Advanced NAFLD patients have been shown to consume more carbohydrates/energy higher saturated fatty acid and lower polyunsaturated fatty acids [77,78]. Adipose tissue in NAFLD produces adipokines, such as tumor necrosis factor alpha (TNFα), resistin, and adiponectin.…”
Section: Oxidative Stress In the Pathogenesis Of Nafld-related Steatomentioning
confidence: 99%
“…Similar to VC and VD, VB6 was also negatively correlated with the risk of NAFLD. Federico et al found that patients with NASH had a less daily intake of VB6 than those in the control group ( 41 ). A prospective clinical study suggested that an oral VB6 supplement could significantly ameliorate liver fat accumulation in patients with NAFLD ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of carbohydrates, especially fructose, worsen insulin sensitivity and increase de novo lipogenesis (DNL). Unbalanced lipid intake leads to alterations in redox status and ROS production [ 30 , 31 ].…”
Section: Triggers Of Liver Inflammationmentioning
confidence: 99%